Global warming responses of gut microbiota in moose (Alces alces) populations with different dispersal patterns. (15th June 2022) - Chen, S.; Holyoak, M.; Liu, H.; Bao, H.; Ma, Y.; Dou, H.; Li, G.; Roberts, N. J.; Jiang, G.
Abstract: While dispersal is the basis of inter‐population connectivity, it is difficult to directly observe. New molecular techniques provide ways of studying the intensity and direction of dispersal among populations through quantifying gene flow. When herbivores disperse their gut microbes travel with the host, and gut microbiota is known to play an important role in host health. However, the current understanding of the driving mechanism between moose dispersal patterns and gut microbial structure is vague. Therefore, when we observe the effects of climate warming on gene flow, it is important to understand the ecological mechanisms that affect the gut microbiota. We applied integrative methods from molecular biology, nutritional ecology and microbiomics to quantify dispersal patterns of moose populations in northeast China and explore the ecological mechanisms driving gut microbe–host associations. We found that moose populations in northeast China are undergoing two dispersal patterns while retreating in a northwesterly direction. Dispersing and isolated moose populations differed in their gut microbial composition and frequency of functional types that relate to digestion and diet composition. We also found that the environmental variables related to the moose gut microbial communities also changed with different dispersal patterns. The gut microbiota of isolated moose populations was only related to ambient temperature, whereas the microbiota in dispersing moose populations was related to longitude and diet protein content. We expect that the differences in the taxonomic and functional structure of gut microbiota relating to digestion are adaptive. Consequently, this study highlights that special attention should be placed on the management of isolated moose populations, and ecological corridors or translocation of moose individuals may be needed to allow persistence in the face of global warming; doing this will likely improve the adaptability of gut microbiota. Abstract : Understanding the ecology of animal dispersal becomes ever more pressing when we consider the diverse and powerful effects of climate on dispersal. However, the current understanding of the driving mechanisms between moose dispersal patterns and gut microbial structure is vague. We explored the ecological relationship between gut microbiota and moose dispersal patterns, and found that the moose population in Northeast China may have coexisted in two dispersal patterns under the general trend of retreating northeast. Furthermore, the environmental variables related with the moose gut microbial communities change with different dispersal patterns. Therefore, the gut microbiota plays a crucial role in host phenotypic plasticity under different dispersal patterns, and may be influencing vertebrate host evolution. This study highlights that special attention should be placed on isolated populations of moose, and ecological corridors or translocation of individuals may be needed for moose conservation to allow persistence in the face of global warming.